The Effect of Principals’ Academic Supervision and Teachers’ Discipline on Teachers’ Teaching Performance in Junior High Schools - Noprianti Noprianti; Rambat Nur Sasongko; Asti Putri Kartiwi (Journal of Social Work and Science Education, 2026)
Improving teacher performance in resource-constrained rural schools remains a critical challenge. While principal supervision and teacher discipline are acknowledged factors, their combined and relative impact in such contexts is poorly understood. Utilizing a census of all teachers (N=85) from three public junior high schools in Kedurang District, Indonesia, this study employed multiple regression analysis on survey data. Results indicated that teacher discipline (β = 0.712, p < .001) was a significant positive predictor of teaching performance. Academic supervision showed a positive but non-significant relationship (β = 0.027, p = .797). Together, both variables explained 56.2% of the variance in teaching performance (R² = 0.562, p < .001). Teacher discipline alone accounted for 56.2% of the variance, while academic supervision contributed 33.0% when examined individually. This study addresses the gap in understanding how supervisory practices and professional discipline operate in non-urban Indonesian junior high schools, revealing that teacher discipline is the dominant factor while supervision’s effect is context-dependent. The results suggest that school principals in rural settings should prioritize reinforcing teacher discipline while improving the quality and developmental orientation of academic supervision to maximize teaching performance. The study underscores the necessity of integrated leadership strategies that combine developmental supervision with fostering intrinsic professional discipline to enhance teaching quality in rural settings.